2021
DOI: 10.1186/s13049-020-00824-8
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking behaviors and provider outcomes in emergency department physicians: two consecutive, observational and multi-source studies

Abstract: Background Multitasking is a key skill for emergency department (ED) providers. Yet, potentially beneficial or debilitating effects for provider functioning and cognition are underexplored. We therefore aimed to investigate the role of multitasking for ED physicians’ work stress and situation awareness (SA). Methods Two consecutive, multi-source studies utilizing standardized expert observations in combination with physicians’ self-reports on stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The working model in the ED has classically been described as multitasking, with frequent interruptions a major consequence [30]. This last aspect was recognized by the respondents as a factor affecting safety [31]. Our survey confirmed the relevance of such interruptions; 54.4% of respondents reported that interruptions always disrupted the ability of staff to provide care.…”
Section: Discussionsupporting
confidence: 68%
“…The working model in the ED has classically been described as multitasking, with frequent interruptions a major consequence [30]. This last aspect was recognized by the respondents as a factor affecting safety [31]. Our survey confirmed the relevance of such interruptions; 54.4% of respondents reported that interruptions always disrupted the ability of staff to provide care.…”
Section: Discussionsupporting
confidence: 68%
“…Emergency physicians determine the need for admission based upon a complex interaction of clinical and psychosocial factors, response to therapy and judgement 22 while often multitasking and working in a challenging environment 24 . Cognitive errors and poor decision‐making can occur 25 and the use of predictive algorithms may reduce the potential for error while improving patient safety 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study found that ED physicians engaged between 13% and 19% of their work time in multitasking. After controlling for ED workload, they found that physicians who engaged more frequently in multitasking perceived higher work stress [ 15 ].…”
Section: Discussionmentioning
confidence: 99%